Recognition of hemodynamic change at a brief glance in Budd–Chiari syndrome by 4D flow MRI - Minami Kinjo, MD; Nanae Tsuchiya, MD, PhD; Hitoshi Inafuku, MD, PhD; Tatsuya Maeda, MD; Yukari Tomori, MD, PhD; Akihiro Nishie, MD, PhD (Radiology Case Reports)
Budd–Chiari syndrome (BCS) is characterized by obstruction or stenosis of the major hepatic veins or the hepatic inferior vena cava (IVC). A man in his 30s with BCS, presenting with occlusion of the hepatic IVC and the right and left hepatic veins on computed tomography, underwent assessment using 4-dimensional flow magnetic resonance imaging (4D flow MRI) before and after IVC reconstruction and hepatic vein recanalization. Preoperative 4D flow MRI revealed complex hemodynamics and membranous stenosis with jet flow between the middle hepatic vein (MHV) and the right atrium (RA), indicating severe narrowing. Postoperative 4D flow MRI demonstrated blood flow from the IVC and MHV to the RA. In this case, 4D flow MRI allowed rapid visualization of hemodynamic changes associated with BCS.